2016
DOI: 10.1155/2016/2932049
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Associations betweenXPCGene Polymorphisms and Neuroblastoma Susceptibility in a Chinese Population

Abstract: Neuroblastoma is one of the most malignant solid tumors in infants and young children. No more than 40% of neuroblastoma patients can survive for longer than five years after it has been diagnosed. XPC protein is a pivotal factor that recognizes DNA damage and starts up the nucleotide excision repair (NER) in mammalian cells. This makes up the first group to defend against the cancer. Previous studies have identified that XPC gene polymorphisms were associated with various types of cancer. However, the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…For instance, there are a total of 33 articles with 14877 cases and 17888 controls [1,28,30–32,36,39,42,44,45,47,48,50,54–56,60,64–66,68–70,72,75–79,82,93–95] for the prior meta-analysis of He et al in 2013 [15]. In this study, we excluded two articles regarding bladder cancer [95] and cutaneous melanoma [94] because the genotype distribution in the control group is not in line with the HWE, and we added 32 other published articles [4,10,11,27,29,33–35,37,38,40,41,43,46,49,51,52,57–59,61–63,67,71,73,74,80,81,83–85]. Our pooling data from eight case–control studies showed the genetic correlation between XPC rs2228000 and increased risk of bladder cancer under the allelic, homozygotic, heterozygotic, dominant, and recessive models, which is partly consistent with the positive data of He et al (2013) [15] under the homozygotic and recessive models from four case–control studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, there are a total of 33 articles with 14877 cases and 17888 controls [1,28,30–32,36,39,42,44,45,47,48,50,54–56,60,64–66,68–70,72,75–79,82,93–95] for the prior meta-analysis of He et al in 2013 [15]. In this study, we excluded two articles regarding bladder cancer [95] and cutaneous melanoma [94] because the genotype distribution in the control group is not in line with the HWE, and we added 32 other published articles [4,10,11,27,29,33–35,37,38,40,41,43,46,49,51,52,57–59,61–63,67,71,73,74,80,81,83–85]. Our pooling data from eight case–control studies showed the genetic correlation between XPC rs2228000 and increased risk of bladder cancer under the allelic, homozygotic, heterozygotic, dominant, and recessive models, which is partly consistent with the positive data of He et al (2013) [15] under the homozygotic and recessive models from four case–control studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although more than 70 case–control studies were enrolled in the overall meta-analysis, small sample sizes were still included in some subgroup analyses. For example, only two case–control studies [56,74] were included for the subgroup of ‘blood system cancer’, while only two studies [81,83] were enrolled for ‘nervous system cancer’. Therefore, we still cannot rule out the possible genetic role played by XPC rs2228000 in the risk of cancers of the blood or nervous systems.…”
Section: Discussionmentioning
confidence: 99%
“…All cases were unrelated ethnic Chinese Han individuals and recruited from the Guangzhou Women and Children's Medical Center between March 2001 and June 2016. We also included a total of 531 age‐, gender‐, race‐matched cancer‐free volunteers recruited from the same hospital . Each individual donated 2 mL blood for genomic DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Controls were chosen from children who visited for routine physical examination, as we described previously. 24 29 A total of 531 ethnicity-, age-, and gender-matched cancer-free controls were included in the study. Written informed consent was obtained from all subjects or their legal guardians in accordance with the principles of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%